2019
DOI: 10.1128/jb.00495-19
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine Biosynthesis in Mitis Group Streptococci via Host Metabolite Scavenging

Abstract: We lack fundamental information about the composition of the cellular membrane even for the best-studied pathogens of critical significance for human health. The mitis group streptococci are closely linked to humans in health and disease, but their membrane biology is poorly understood. Here, we demonstrate that these streptococci scavenge major human metabolites and use them to synthesize the membrane phospholipid PC. Our work is significant because it identifies a mechanism by which the major human pathogen … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(86 citation statements)
references
References 72 publications
1
85
0
Order By: Relevance
“…The gene cdsA is required for the synthesis of CDP-DAG, which is then converted by PgsA to produce phosphatidylglycerophosphate (PGP), the immediate precursor of PG ( Fig. 1A) (18,41). We previously reported that cdsA deletion mutants of S. mitis and S. oralis do not synthesize PG, nor does a pgsA deletion mutant of SM43 (18, 41) ( (Table 1).…”
Section: Biosynthesis Of (Gro-p)-dihexosyl-dag Requires Phosphatidylgmentioning
confidence: 99%
See 2 more Smart Citations
“…The gene cdsA is required for the synthesis of CDP-DAG, which is then converted by PgsA to produce phosphatidylglycerophosphate (PGP), the immediate precursor of PG ( Fig. 1A) (18,41). We previously reported that cdsA deletion mutants of S. mitis and S. oralis do not synthesize PG, nor does a pgsA deletion mutant of SM43 (18, 41) ( (Table 1).…”
Section: Biosynthesis Of (Gro-p)-dihexosyl-dag Requires Phosphatidylgmentioning
confidence: 99%
“…Extraction of total lipids from stationary phase cells was performed by acidic Bligh-Dyer extraction as previously described (18). Specifically, cells were grown to stationary phase, The MS/MS analysis used nitrogen as the collision gas.…”
Section: Lipidomics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Since PC synthesis by the CDP-choline pathway is unique for certain species of Treponema [97], it is important to know the other pathways for PC synthesis that have been reported in prokaryotes. There are three other pathways for PC synthesis in bacteria (Figures 3(a)-3(c)) [54,84,86]. The PE methylation pathway (Figure 3(a)) [54,83], where PC is synthesized from PE in a sequence of three steps catalyzed by phospholipid N-methyltransferase (PLMT) with methyl donor S-adenosylmethionine (SAM) to form monomethylphosphatidylethanolamine (MMPE), dimethylphosphatidylethanolamine (DMPE), and then PC [54].…”
Section: Chok In Bacterial Lipid Biosynthetic Pathwaysmentioning
confidence: 99%
“…CDP-DAG on the other hand is produced from PA by CDP-DAG synthase [54] Secondly, the phosphatidylcholine synthase (Pcs) pathway (Figure 3(b)) [99] is comprised of a single step of condensing CDP-DAG with Cho by the Pcs enzyme [54,99]. Finally, the glycerophosphorylcholine (GPC) pathway (Figure 3(c)) [54,86] was reported only in X. campestris [98], S. mitis, and S. oralis [86]. In X. campestris, extracellular GPC is transported and converted via two-step acyl-CoAdependent acylation to lysophosphatidylcholine (LPC) by unknown enzymes and then to PC by acyltransferases Xc_ 0188 and Xc_0238 [98].…”
Section: Chok In Bacterial Lipid Biosynthetic Pathwaysmentioning
confidence: 99%